Comparative study of heroin and ecstasy abusers in the SAF - Ip, Lee Lee. (2008)
This study aimed to understand the ecstasy and heroin abusers in the SAF in terms of six factors, namely, demographic profile, family background, social factors, addiction history, abstention history and social support network. A questionnaire was developed to explore these factors. Data collection was based on personal interviews with 31 heroin abusers and 32 ecstasy abusers.